Soil amendments improve vegetation establishment and evapotranspiration on store and release mine cover systems - Millar, C; Barber, L; Robeson, M; Sump, D; McDonnell, JJ (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
Keywords: mine cover systems, surface amendments, land reclamation, vegetation establishment, ecohydrology, net percolation, evapotranspiration